(untitled) (Conferencea, 2023)
The article notes that pedagogy is the science of raising and educating a person, especially during childhood and adolescence, and the subject of pedagogy is the holistic pedagogical process of directed development and formation of a person in the conditions of education, training and education. It is also said that since the army appeared as a unique social phenomenon, the most important component of military activity has been and will remain the training and education of personnel. In fact, this is practical military pedagogy, a necessary, mandatory means of comprehensive training of soldiers for the successful conduct of combat operations.